Four Styles of Regulation and their Implications for Comparative Policy Analysis. Issue 4 (8th August 2017) - Adam, Christian; Hurka, Steffen; Knill, Christoph
Abstract: Comparative research crucially depends on the availability of meaningful descriptive concepts capturing the essence of empirical phenomena. In policy analysis, the portfolio of classical concepts describing policy contents and procedures remains unmatched by a similar pool of concepts available for describing patterns of regulatory outputs. Starting from the premise that policy-makers not only create behavioral rules, but also define sanctions for rule violations, this article distinguishes four ideal-typical styles of regulation: authority, lenient authority, punitive permissiveness, and permissiveness. It uses handgun regulation to illustrate the merits of this distinction and discusses the theoretical implications of the approach.